Identification of Bioactive Components in Ethanolic and Aqueous Extracts of Amorphophallus campanulatus Tuber by GC-MS Analysis - Subhashree Basu; Utpal Roychoudhury; Moumita Das; Gouriprosad Datta (International Journal of Phytomedicine, 2013)
The uses of herbal medicines worldwide provide an excellent opportunity for India to look into the therapeutic compounds from ancient system of therapy, Ayurveda. Since ancient time, Amorphophallus campanulatus has been considered as medicinal plant with multiple protective activities. So, the present study was aimed to identify the various phytochemical constituents in the ethanolic and aqueous extracts of Amorphophallus campanulatus tuber by GC-MS analysis. The ethanolic and aqueous extracts of Amorphophallus campanulatus were dissolved in absolute ethanol (1mg/ml). 10µl of this sample was then injected for gas chromatography- mass spectrometric (GC-MS) analysis. The results for the first time revealed the presence of several bioactive components both in the ethanolic as well as in the aqueous extracts. However, the ethanolic extract showed quantitatively higher amount of these components than the aqueous extract as is clearly indicated by higher % peak area of the compounds in the ethanolic extract. Some components of biological importance include Hexadecanoic acid and its methyl and ethyl esters, Heptadecanoic acid, Linoleic acid and its ester, Oleic acid, Stigmasterol, 1, 3, 5, benzenetriol, 4H-Pyran-4-one, 2, 3-dihydro-3, 5 -dihydroxy-6-methyl-, Squalene and Vitamin E. Thus the results of the present study is an evidence to support the traditional usage of A. campanulatus which possess several known and unknown bioactive components. By identifying and isolating these components, new drugs can be formulated to treat various diseases.